2016
DOI: 10.1002/2016jg003570
|View full text |Cite
|
Sign up to set email alerts
|

Historical trends of forest fires and carbon emissions in China from 1988 to 2012

Abstract: A larger amount of carbon is stored in forest ecosystems than in the entire atmosphere. Thus, relatively small changes in forest carbon stocks can significantly impact net carbon exchange between the biosphere and atmosphere. Changes in forest stocks can result from various disturbances, such as insect pests, windstorms, flooding, and especially forest fires. Globally, the impact of forest fires has been enhanced due to ongoing warming of the climate. The current study reported an evaluation of carbon emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 77 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, historical fire statistics in Russia and China show a positive fire activity trend in southeastern Siberia over the past few decades, and anthropogenic activity might contribute to this trend ( fig. S3) (30). In addition, this region has experienced long-term spring warming (31) and earlier snowmelt (32,33) due to Arctic warming.…”
Section: Fire Activity Related To Ariditymentioning
confidence: 99%
“…On the other hand, historical fire statistics in Russia and China show a positive fire activity trend in southeastern Siberia over the past few decades, and anthropogenic activity might contribute to this trend ( fig. S3) (30). In addition, this region has experienced long-term spring warming (31) and earlier snowmelt (32,33) due to Arctic warming.…”
Section: Fire Activity Related To Ariditymentioning
confidence: 99%
“…Therefore, the accurate estimation and detailed analysis of forest fire emissions still need to be improved.Streets et al [8] found that forest fire emissions were the primary source of biomass emissions in Asia, and that China had the highest biomass burning emissions in Asia. Some research has addressed forest fire emissions in China, but most of these studies have only estimated and analyzed the carbon emissions from forest fires [22,23]. Moreover, there is a lack of current and detailed regional forest fire emissions inventories.…”
mentioning
confidence: 99%
“…Wildfires occur much more frequently in the south than in the north, while burned area has an opposite spatial pattern (Chang et al, 2015;Chen et al, 2017;Li et al, 2015;Lv et al, 2006;Tian et al, 2013). Many regions have two fire seasons in spring and fall and large interannual variability (Niu & Zhai, 2012;Yi et al, 2017) due to local, regional, and global atmospheric processes (Yao et al, 2017;Zhang et al, 2016). Efforts have been made to use atmospheric factors to predict seasonal fire activity in China (Chang et al, 2013;Li et al, 2014;Sun & Zhang, 2018).…”
Section: 1029/2019gl081932mentioning
confidence: 99%